Enhancing mummy 'palaeobiographies' through the use of multidisciplinary techniques and approaches. (February 2023) - White, K.N.; Chiasserini, D.; Loynes, R.; David, A.R.; van Dongen, B.E.; Drosou, K.; Forshaw, R.; Fraser, S.; Causey-Freeman, P.; Metcalfe, J.; Murphy, E.; Regan, M.; et al.
Highlights: Ante-mortem damage to the ribs indicative of a blow by a sharp, possibly curved, object from behind, suggesting that Takabuti was murdered. mtDNA revealed the rare Eurasian H4a1 haplogroup suggestive of the introduction of new gene pools during the Late Period of ancient Egyptian history. Proteomics indicate protracted leg muscle activity in the hours before death. Chemical analysis and microscopy of packing material inserted during mummification discovered wood shavings, including imported cedar, and congealed resin.The resin was identical to the mummification balm from the original bandages. Packing material's radiocarbon date indicated mummification in the Third Intermediate Period and in keeping with the previously dated hair and the stylistic dating of the coffin that placed it in the 25th Dynasty. Abstract: Scientific examination of mummies has provided a better understanding of the ancestry, diet, disease, medical practices, mummification processes, culture and society of human populations worldwide and from different epochs. However, many examinations have been invasive and/or destructive, leading to current-day concerns among archaeologists and mummy custodians about this methodology. Multidisciplinary approaches, notably minimally invasive biopsy, endeavour to maximise the amount of data obtained from a sample whilst minimising its size and the effects on the mummy. As an illustration of the wealth of data that can be obtained from non- and minimally invasive image-guided procedures on wrapped mummified bodies, we report here on such a study of Takabuti, an Egyptian woman who lived in Thebes during the first millennium BCE. Multiplanar and 3D reconstructive computerised whole-body tomographic imaging (CT) revealed age at death and confirmed the inscriptional evidence from the coffin regarding sex. A notable finding was ante-mortem damage to the ribs indicative of a blow by a sharp, possibly curved, object from behind, suggesting that Takabuti was murdered. Fifty milligrams of bone and thigh muscle were taken for respectively genomic and proteomic analysis. mtDNA revealed the rare Eurasian H4a1 haplogroup suggestive of the introduction of new gene pools during the Late Period. Identification and quantification of the structural and functional proteins and metabolically important enzymes indicate protracted leg muscle activity in the hours before death. Chemical analysis, microscopy and radiocarbon dating of 20–30 mg needle biopsy samples of the packing material inserted during mummification discovered wood shavings, including imported cedar, and congealed resin. Organic analyses revealed the resin to be largely vegetal in origin including wood and aromatic/preservative oils derived from Pinaceae species, identical to the mummification balm removed from the original bandages. Once the age of the trees from which the sawdust was derived has been taken into account, the packing material's radiocarbon date indicated mummification in the Third Intermediate Period and in keeping with the previously dated hair and the stylistic dating of the coffin that placed it in the 25th Dynasty. We have shown that CT scanning combined with targeted invasive biopsy needle sampling provides a wealth of scientific information with minimal disturbance to the mummy. Molecular, biochemical and geochemical analytical techniques allow statistically robust replicate sampling but require the removal of only milligram quantities. This approach forms the basis of a generic 'palaeobiographical' approach to the examination of naturally and artificially preserved bodies in which both soft tissues and bone are present.